Production of and responses to unimodal and multimodal signals in wild chimpanzees, Pan troglodytes schweinfurthii. (January 2017) - Wilke, Claudia; Kavanagh, Eithne; Donnellan, Ed; Waller, Bridget M.; Machanda, Zarin P.; Slocombe, Katie E.
Abstract : Animals communicate using a vast array of different signals in different modalities. For chimpanzees, vocalizations, gestures and facial expressions are all important forms of communication, yet these signals have rarely been studied together holistically. The current study aimed to provide the first comprehensive repertoire of flexibly combined ('free') multimodal (MM) signals, and assess individual and contextual factors influencing production of, and responses to, unimodal (UM) and MM signals in wild chimpanzees. In total, 48 different free MM signals were produced. MM signals were produced at a significantly lower rate than UM signals, but 22 of 26 focal animals were observed to produce free MM signals. The relative production rates of different types of UM and MM signals differed significantly between the behavioural contexts investigated, showing flexible use of signals across contexts. In contrast, individual factors such as age, sex or rank of signaller did not appear to influence the type of signal produced or the likelihood of eliciting a response. Finally, we compared recipient responses to free MM grunt-gesture signals and matched UM component signals and found that these MM signals were more likely to elicit a response than a grunt alone, but were as likely to elicit a response as the gesture alone. The overall findings point to a widespread capacity for wild chimpanzees to flexibly combine signals from different modalities and highlight the importance of adopting a multimodal approach to studying communication. Highlights: Repertoire of 48 'free' multimodal (MM) signals documented in wild chimpanzees. MM signals were produced at significantly lower rates than unimodal (UM) signals. Chimpanzees show flexible usage of UM and MM signals across behavioural contexts. Response more likely to MM grunt-gesture than grunt alone, but not gesture alone.